If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6d + 3d = 9 Combine like terms: 6d + 3d = 9d 9d = 9 Solving 9d = 9 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Divide each side by '9'. d = 1 Simplifying d = 1
| 105=-7p-7(p-7) | | 3(x-4)=108 | | x+6y=134 | | u/4-2=1 | | -6-6x=3+3x | | 70=12x-2 | | (r+5)(r-6)= | | 4q-7=5 | | Log(x+3)-4=2 | | -3y=4x+12 | | 5w-2x=19 | | x-4x+m+1=0 | | 55w-2x=19 | | 4(x-2/5)=20 | | Ln(3x-2)=7 | | 2(x+1)=162 | | Tgx=3/4 | | -195/-26 | | Log(x)=-.75 | | 9/4-2=2 | | x+(x+1)+(x+2)+(x+3)+(x+4)+(x+5)=0 | | 5-2(2k+1)=5-(k-1) | | 13.7b-3=3-4.2b | | X=17x+12 | | 22x+3=9+21x | | 2=2j-4 | | 8(9x-5)=2(5x+6) | | 4.4r+48.004=7.8(.06r-1.82)-6.5r | | 5x+7=5x-9 | | 108=4(3-6k) | | (2x^2+4x-2)-(5x^2+6x+3)+(-2x^2-3x-5)= | | 4x-25=x+8 |